PREPARATION OF PLASMA MEMBRANE FROM ISOLATED NEURONS - Henn, Fritz A. (The Rockefeller University Press, 1972)
A bulk fraction enriched with respect to neuronal cell bodies was used as starting material for the isolation of neuronal plasma membrane The cells were gently homogenized in isotonic sucrose and a crude membrane containing fraction sedimented at 3000 g. Subsequently, the membrane fraction was purified on a discontinuous sucrose density gradient between 35% and 25 5% sucrose (w/w). Enzymatic analyses showed a 4–5-fold enrichment in plasma membrane markers, and a 10–15% contamination of mitochondrial and microsomal material. Electron micrographs of the membrane fraction confirmed the enzymatic data Fragmented membranes were found, mainly in vesicular form No ribosomes, but a few mitochondria and some multilamellar membranes were seen